MACHINE LEARNING UNTUK PENDIDIKAN: MENGAPA DAN BAGAIMANA - Apit Fathurohman (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2021)
Machine Learning is a subset of artificial intelligence (AI) that helps computers or teaching machines learn from all previous data and make intelligent decisions. Machine learning frameworks require capturing and maintaining a rich set of information and turning it into a structured knowledge base for different uses in various fields, one of which is in education. The purpose of this article is to answer the questions 1) Why is Machine Learning Important for Education? and 2) How is Machine Learning Utilized for Education? This article uses a qualitative method with data collection techniques with literature study. Based on the results of the literature study, machine learning in the field of education has many advantages and advantages, where teachers can save time in learning activities in the classroom. Machine Learning encourages depersonalized learning in the context of educational deployment. Machine Learning enables teachers to gain a better understanding of their students' progress in learning